First high–resolution comprehensive analysis of 72GeH4 spectra in the Dyad and Pentad regions. (March 2019) - Ulenikov, O.N.; Gromova, O.V.; Bekhtereva, E.S.; Raspopova, N.I.; Kuznetsov, A.V.; Koshelev, M.A.; Velmuzhova, I.A.; Sennikov, P.G.
Highlights: High resolution analysis of the Dyad and Pentad of 72 GeH4 . Resonance interactions in spherical top molecules. Determination of spectroscopic parameters. 9112 line positions of the 11 vibrational states of 72 GeH4 . Abstract: The spectra of germane 72 GeH4 enriched up to 99.9% in the sample were recorded with high resolution (0.003 cm − 1 ) at different pressures with the Bruker IFS 125HR Fourier transform spectrometer (Nizhny Novgorod, Russia). The region of 700–4400 cm − 1, where the Dyad and Pentad are located, was theoretically analyzed. The 9112 transitions belonging to the seven "cold" bands (6761 transitions) of the Dyad and Pentad and to the nine "hot" Dyad–Pentad bands (2351 transitions) were assigned and analyzed with an effective hamiltonian model which takes into account the presence of resonance interactions. The obtained set of 53 fitted parameters reproduces the initial 9112 experimental line positions with a d r m s = 2.44 × 10 − 4  cm − 1 .